Analisis faktor keberhasilan implementasi E-Health menggunakan model HOT-fit - Nurramadhani, Latifa; Tambotoh, Johan J.C. (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
The development of information technology has brought significant changes to the public sector in both developed and developing countries. In the healthcare sector, there is E-Health to improve service quality by providing information and registration of health services, including drug prescriptions and disease information that the public can access through electronic devices equipped with the Internet. This study aims to identify the success factors of E-Health as one of the E-Government systems considered successfully implemented in Indonesia through user satisfaction to strengthen the effectiveness of E-Health. This study used a modified HOT-fit (Human, Organization, Technology, and fit) model with six variables and quantitative methods. Four of the nine hypotheses were rejected based on data collected from 120 respondents and statistical analysis using Smart Partial Least Squares 3.2.9. It indicates that information quality and service quality have a significant positive effect on user satisfaction and net benefits through user satisfaction.